Hybrid Signaling-Droop DC-Link Voltage Control for Trains With Multiple Onboard Power Sources - Saad Ahmad; Mariam Saeed; Juan Manuel Guerrero; Iker Muniategui-Aspiazu; Guillermo Nunez; Igor Larrazabal; Fernando Briz (IEEE Access)
The increasing trend in efficiency and performance requirements of electric trains is leading to the deployment of more onboard energy storage elements. Hydrogen fuel cells along with battery systems are being considered by several train manufacturers. Control of the dc-link connecting all energy sources and loads can be challenging due to the need to guarantee reliable operation in all possible scenarios. This paper presents a dc-link control strategy for trains with multiple energy sources. The proposed method combines the advantages of dc bus signalling and droop methods, and allows smooth enabling and disabling of power sources by voltage command modification without any change in the overall control structure. Further, it is fault tolerant to communication loss between the battery and the central control. The proposed concepts are validated in multiple scenarios by means of simulation, as well as experimentally using a down-scaled test bench.